Numerical Study on the Use of Shear-Thinning Nanofluids in a Micro Pin-Fin Heat Sink Including Vortex Generators and Changes in Pin Shapes - Castillo-Del Barrio, E; Gonzalez-Andres, A (ELSEVIER, 2022)
Background: The use of passive strategies in microchannel heat sinks allows for increasing the device s efficiency. The combined use of vortex generators, change of shape of the pins, and shear-thinning nanofluids allow increasing the mixing capacity of the flow without a significant increase in the pressure drop. Method: In this study, we numerically investigated the use of water and two hybrid shear-thinning nanofluids in a microchannel heat sink. In addition, the use of vortex generators in the vertical walls of the microchannel and the change in pin shape from circular to hexagonal was evaluated. The simulations were performed in three dimensions with largescale meshes without considering symmetry. Findings: From the studied cases, the addition of vortex generators increased the heat transfer rates significantly (by more than 20%) with a considerable increase in pressure drops in the Newtonian fluid. By contrast, in shear-thinning fluids, the pumping cost is reduced by an average of 20%.